Identification and functional analyses of drought stress resistance genes by transcriptomics of the Mongolian grassland plant Chloris virgata - Ganbayar Namuunaa; Baldorj Bujin; Ayumi Yamagami; Byambajav Bolortuya; Shintaro Kawabata; Hirotaka Ogawa; Asaka Kanatani; Minami Shimizu; Anzu Minami; Keiichi Mochida; Takuya Miyakawa; Bekh-Ochir Davaapurev; et al. (BMC Plant Biology)
Abstract Background Mongolian grasslands, including the Gobi Desert, have been exposed to drought conditions with few rains. In such harsh environments, plants with highly resistant abilities against drought stress survive over long periods. We hypothesized that these plants could harbor novel and valuable genes for enhancing drought stress resistance. Results In this study, we identified Chloris virgata, a Mongolian grassland plant with strong drought resistance. RNA-seq-based transcriptome analysis was performed to uncover genes associated with drought stress resistance in C. virgata. De novo transcriptome assembly revealed 25,469 protein-coding transcripts and 1,219 upregulated genes after 3- and 6-hr drought stress treatments. Analysis by homology search and Gene Ontology (GO) enrichment indicated that abscisic acid (ABA)- and drought stress-related GO terms were enriched. Among the highly induced genes, ten candidate cDNAs were selected and overexpressed in Arabidopsis. When subjected to drought stress, three of these genes conferred strong drought resistance in the transgenic plants. We named these genes Mongolian Grassland plant Drought-stress resistance genes 1, 2, and 3 (MGD1, MGD2, and MGD3). Gene expression analyses in the transformants suggested that MGD1, MGD2, and MGD3 may activate drought stress-related signalling pathways. Conclusion This study highlighted the drought resistance of C. virgata and identified three novel genes that enhance drought stress resistance.